2019
DOI: 10.3390/d11090154
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping-by-Sequencing Reveals Molecular Genetic Diversity in Italian Common Bean Landraces

Abstract: The common bean (Phaseolus vulgaris L.) is one of the main legumes worldwide and represents a valuable source of nutrients. Independent domestication events in the Americas led to the formation of two cultivated genepools, namely Mesoamerican and Andean, to which European material has been brought back. In this study, Italian common bean landraces were analyzed for their genetic diversity and structure, using single nucleotide polymorphism (SNP) markers derived from genotyping-by-sequencing (GBS) technology. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 68 publications
2
16
0
Order By: Relevance
“…Polymorphisms were widely distributed across the 11 chromosomes and were highly correlated with the length and number of genes on each chromosome. The transition/transversion rate was consistent with that observed in other studies on common bean and other species 28 , 35 , 52 , 53 . Transitions are usually more frequent than transversions in several species, which indicates that the former are better tolerated during natural selection, which may be due to the fact that they are synonymous mutations in protein-coding sequences 29 , 54 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Polymorphisms were widely distributed across the 11 chromosomes and were highly correlated with the length and number of genes on each chromosome. The transition/transversion rate was consistent with that observed in other studies on common bean and other species 28 , 35 , 52 , 53 . Transitions are usually more frequent than transversions in several species, which indicates that the former are better tolerated during natural selection, which may be due to the fact that they are synonymous mutations in protein-coding sequences 29 , 54 .…”
Section: Discussionsupporting
confidence: 91%
“…Genetic differentiation between common bean accessions based on the gene pool has been well documented in several previous studies 3 , 34 , 35 , 57 60 . The relationship between the genetic similarity of the Mesoamerican accessions and the color of the seed tegument was also observed by Valdisser et al 61 and Gioia et al 62 .…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…We identified several regions on chromosomes Pv02, Pv07, Pv09, and Pv11 where F ST values exceeded 0.5. Similarly, in a study of genetic diversity of Italian bean landraces, Lioi et al [ 64 ] reported that genomic regions related to domestication were concentrated on Pv02, Pv07, and Pv09 for Mesoamerican types. For comparisons between wild and domesticated bean landraces, Papa et al [ 65 ] also reported significantly larger levels of F ST differentiation around genomic regions associated with domestication.…”
Section: Discussionmentioning
confidence: 99%